Approaches to evaluate spatial and temporal variability of deep marine sediment characteristics under the impact of dense water formation events - DURRIEU de MADRON, XAVIER; STABHOLZ, MARION; HEIMBÜRGER-BOAVIDA, LARS-ERIC; AUBERT, DOMINIQUE; KERHERVÉ, PHILIPPE; LUDWIG, WOLFGANG (Mediterranean Marine Science, 2020)
Dense shelf water cascading and open-ocean convection frequently occur in the Gulf of Lions, Northwestern Mediterranean Sea. These intense dense water formation events are capable of supplying large amounts of particulate matter as well as remobilizing and dispersing local sediments and are therefore thought to leave an imprint on superficial deposits. Here, we compare the spatial variability of the superficial sediment composition (grain size, organic parameters, and metals) at different scales (from decimetric to kilometric) on the continental slope and rise with the temporal variability linked to the occurrence of intense dense water formation events. The spatial and temporal variability of the geochemical composition of deep sediments was assessed using multivariate and geostatistical analyses. The results indicate that in the outer reaches of Cap de Creus Canyon, where both processes interact, no clear relation was found between the temporal variability of the superficial sediment and the deep-water formation events, and that the small-scale spatial variability of the sediment masks the temporal variability. Measurements across the southern slope indicate the presence of a somewhat distinct geochemical signature that likely results from the influence of recurrent intense, dense water formation events as well as unabating bottom trawling activity.